Mladi bralci in stare zgodbe - Santini, Monica (Primerjalna književnost, 2011)
Who has read Arthurian stories in the last century and who is still enjoying them today? One of the possible answers is: young readers. This paper reviews the choices and changes the authors of twentieth-century Arthurian retellings have made in an effort to adapt the traditional stories to a modern young readership.
Keywords: romance; legende o kralju Arturju; mladinska književnost; young adult literature; angleška književnost; mladi bralci; priredbe